Volatile profile, phenolic content and antioxidant activity of chia seed (Salvia hispanica L.) essential oils obtained by different extraction methods - B. Aydeniz; O. Guneser (Grasas y Aceites)
This investigation aims to reveal the physico-chemical properties and volatile profiles of essential oils derived from chia seeds (Salvia hispanica L.) by employing both hydrodistillation (HDE) and microwave-assisted hydrodistillation (MAHDE) approaches. Microwaves are preferred for seed pre-treatment in HDE, whereas MAHDE uses microwaves directly. Each extraction technique showed different effects on the oil yield, physico-chemical quality parameters, antioxidant capacity and total phenolic content, as well as the volatile profiles of the essential oils. Although chia essential oils extracted by HDE have three and five times more total phenolic (30.6 mg GAE/kg oil) and antioxidant capacity (62.7 μM Trolox/100 g oil) values than these of MAHDE, chia essential oils extracted by MAHDE had a higher distinct effect on the yield (4.20%) of essential oils and prevented the loss of volatile compounds. Both essential oils were subjected to GC-MS analysis, which identified 40 and 48 volatile compounds (mainly as linalool, mesitylene, anethol, cumene, eugenol, β-ocimene, eugenol acetate) in HDE and MAHDE, respectively. The results of this study contribute to the potential use of chia essential oil as a valuable raw material in the food & nutrition, pharmaceutical and cosmetic industries. This research represents the first documentation of the volatile profile of chia seed essential oil.